Effects of diagnostic ultrasound with cRGD-microbubbles on simultaneous detection and treatment of atherosclerotic plaque in ApoE−/− mice - Guo, Shengcun; Zhang, Shengye; Chen, Kui; Chen, Xi; Hu, Fudong (Frontiers in Cardiovascular Medicine, 2022)
Background Atherosclerotic vulnerable plaque is the leading cause of acute fatal cardiovascular events. Thus, early rapid identification and appropriate treatment of atherosclerotic plaque maybe can prevent fatal cardiovascular events. However, few non–invasive molecular imaging techniques are currently available for the simultaneous detection and targeted treatment of atherosclerotic plaques. We hypothesized that diagnostic ultrasound (DU) combined with cyclic Arg-Gly-Asp-modified microbubbles (MBR) could provide targeted imaging and dissolution of activated platelets to identify advanced atherosclerotic plaques and improve plaque instability. Methods Three mouse models, apolipoprotein E-deficient mice on a hypercholesterolemic diet (HCD) or normal chow diet and wild-type mice on an HCD were used. The most appropriate ultrasonic mechanical index (MI) was determined based on the expression of GP IIb/IIIa in sham, DU alone and DUMBR-treated groups at MI values of 0.5, 1.5, and 1.9. The video intensity (VI) values, activated platelets and plaque instability were analyzed by ultrasound molecular imaging, scanning electron microscopy and histopathological methods. Results We found that the VI values of ultrasound molecular imaging of MBR were positively correlated with plaque GP IIb/IIIa expression, vulnerability index and necrotic center / fiber cap ratio. 24 h after treatment at different MIs, compared with those of the other groups, both the VI values and GP IIb/IIIa expression were significantly reduced in MI 1.5 and MI 1.9 DUMBR-treated groups. The plaque vulnerability index and necrotic center / fiber cap ratio were significantly decreased in MI 1.5-treated group, which may be due to targeted dissolution of activated platelets, with a reduction in von Willebrand factor expression. Conclusion DUMBR targeting GP IIb/IIIa receptors could rapidly detect advanced atherosclerotic plaques and simultaneously give targeted therapy by dissolving activated and aggregated platelets. This technology may represent a novel approach for the simultaneous identification and treatment of atherosclerotic plaques.